Perkembangan Teknologi Budi Daya Kedelai di Lahan Sawah - Sumarno Sumarno (Puslitbang Tanaman Pangan, 2011)
Soybean Production Technology Development on Wet Land. Soybean has been grown in Indonesia since 1746, as a component of rice crop rotation on wet land, by applying indigenous technology. Until 1960 Indonesia was the third largest soybean producer in the world. However, the planted area is relatively stagnant until now. Based on its development, there are eight alternative technologies available for producing soybean on wet land, varying from a very simple method requiring minimum input and man power, to very intensive technique. To attain soybean self-sufficiency, it is suggested that the expansion of soybean area to be carried out on fallow wet land during the dry season, applying one of the most suitable cultural technique among the eight available alternatives. National campaign for practicing rice-rice-soybean crop rotation on wet land is expected to improve soil fertility, farmer’s income and increase soybean production toward attaining self sufficiency.